2006
DOI: 10.1063/1.2188417
|View full text |Cite
|
Sign up to set email alerts
|

Cantilever temperature characterization in low temperature vacuum atomic force microscope

Abstract: Articles you may be interested inApplication of triangular atomic force microscopy cantilevers to friction measurement with the improved parallel scan method Rev. Sci. Instrum. 80, 023704 (2009); 10.1063/1.3079685Demonstration of low-temperature atomic force microscope with atomic resolution using piezoresistive cantilevers Rev.The frequency response of an atomic force microscope silicon cantilever located in a vacuum cryostat chamber was investigated. The resonance frequency and the peak width were extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…29 Although it might be possible to reconcile these various results by fitting parameters to a thermal hopping model as described in Refs. 34 Similar results are obtained when tips equipped with submicron thermocouples are brought into tunneling contact with a cold substrate. 19, or to the recent model of Barel et al 15 this type of analysis may not be meaningful because it is based on the assumption that the sliding asperity and the substrate are near thermal equilibrium and can be described by a single temperature.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…29 Although it might be possible to reconcile these various results by fitting parameters to a thermal hopping model as described in Refs. 34 Similar results are obtained when tips equipped with submicron thermocouples are brought into tunneling contact with a cold substrate. 19, or to the recent model of Barel et al 15 this type of analysis may not be meaningful because it is based on the assumption that the sliding asperity and the substrate are near thermal equilibrium and can be described by a single temperature.…”
Section: Discussionsupporting
confidence: 62%
“…The behavior of the temperature in the vicinity of the contact point is shown in Fig. 34 The heat current through the tip is approximately 10 W, but the current density is 10 9 W / m 2 , which is more than an order of magnitude higher than the heat flux in an arc welder. The only length scale in the problem is the contact radius R, so the temperature in both the conical tip and the substrate approaches their respective far field values at distances of order R. Table I shows the results of applying Eqs.…”
Section: Discussionmentioning
confidence: 98%
“…The Young's modulus in turn affects the spring constant and resonant frequency of the cantilever. Kazantsev et al 20) observed a significant frequency shift in an AFM cantilever due to thermal coupling to the sample, with sample temperatures ranging from 15 to 399 K. The effect was ascribed to a change in the Young's modulus. Likewise Boyd et al found a 0.5% change in the Young's modulus and a decrease in resonant frequency with temperature over the range of 200 to 290 K. From Boyd et al we derived a linear temperature coefficient for the Young's modulus of −5.55 × 10 −5 (K −1 ).…”
Section: Effect Of Optical Absorption On Resonance Frequency Shiftmentioning
confidence: 99%